PENGEMBANGAN CUSTOMER RELATIONSHIP MANAGEMENT BERBASIS SISTEM E-COMMERCE - Montana, Sugiarto; Noor, Muwasiq Mochamad (Bina Nusantara University, 2010)
PT Dwisanjaya Abadi Mukti is a company engaged in distributing Pertamina lubricating agent with products for industrial and automotive lubricants. Therefore, companies need a Customer Relationship Management E-commerce-based systems, to address the issues of purchasing and service to customers that are still conducted manually. Systems analysis is done through observation interviews, and literature; analysis of survey findings; and identification of information needs from survey. The system is designed to give advantage to the user as to obtain the desired information quickly, to acquire new customers, improve customer relationships, and retain customers; other than that for the company this system reduces operating costs, more efficient time, accessible anytime and anywhere, improving work productivity, increase sales, increase the number of customers, and improve customer satisfaction.Keywords: customer relationship management, e-commerce, front end, back end